Hong Kong Poison Information Centre: Annual Report 2015. Issue 6 (November 2016) - Chan, YC; Tse, ML; Lau, FL
Objective: To report and analyse the poisoning data of Hong Kong Poison Information Centre (HKPIC) in 2015. Methods: In 2015, all poisoning cases received by HKPIC were retrieved from its database [Poison Information and Clinical Management System (PICMS)] for analysis. Results: A total of 3, 960 poisoned cases were analysed. There were 1, 770 male patients (44.7%), 2, 176 female patients (55.0%) and 14 sex unspecified patients (0.4%). The majority of the cases (63.5%) were between 20 and 59 years old. Common causes for poisoning were suspected self-harm/suicidal attempt (38.4%), unintentional exposure (17.4%) and abusive substances use (11.6%). Excluding the common co-ingestant ethanol, the five commonest types of poison were paracetamol, benzodiazepine, household products, zopiclone and Chinese herbal medicine. Most patients were managed with supportive measures, while 16.4% and 16.2% of them were treated by decontamination and antidotes respectively. Majority of the cases had uneventful recovery; 1% resulted in death and 4.3% had major outcomes. Seven interesting cases and one outbreak were discussed. Conclusions: This 10th annual report provided updated epidemiological information on poisoning pattern in Hong Kong and highlighted important changes in comparing with our previous reports.